Reply to Kahng, S.E. Comment on “Lesser et al. Using Stable Isotope Analyses to Assess the Trophic Ecology of Scleractinian Corals. Oceans 2022, 3, 527–546” - Michael P. Lesser; Marc Slattery; Keir J. Macartney (Oceans, 2024)
Kahng [...]

Size Effects on Pumping Rates in High Microbial versus Low Microbial Abundance Marine Sponges - Michael P. Lesser (Oceans, 2023)
Sponges are increasingly recognized as ecologically important on coral reefs as scleractinian corals decline. Most sponge species can be divided into two symbiotic phenotypes which are characterized as high microbial abundance (HMA) or low microbial abundance (LMA) sponges. Sponge species of HMA or LMA symbiotic phenotypes differ not just in their microbiomes, but in other characteristics, including that LMA sponges actively pump at higher rates than HMA sponges based on a standard normalization to size. This dichotomy has recently been questioned because the size range of LMA sponges used to quantify pumping rates during studies on their trophic ecology were exceedingly small, often less than an order of magnitude. Here, both HMA and LMA sponges, across two to three orders of magnitude in sponge volume (mL) or mass (g) were assessed for allometric relationships between sponge size and pumping rates (Q = mL s−1). The scaling analysis of all data sets combined reveals that HMA sponges scale their pumping rates isometrically with size, while LMA sponges scale their pumping rate allometrically. When HMA species are examined separately, however, tropical HMA sponges scaled isometrically, while temperate HMA sponges scaled allometrically. From an ecological perspective, to quantify differences between HMA and LMA sponges for rate functions of interest (e.g., feeding) it is important to remove the effects of size as a covariate, and adjust the Q values of sponges to a standard volume or mass. For multiple species and geographic locations, this analysis shows that LMA sponges always maintain higher Q values. On tropical coral reefs, the differences between HMA and LMA sponges are intrinsic and constrained by strong evolutionary selection resulting in fixed differences in Q, regardless of sponge size.

Using Stable Isotope Analyses to Assess the Trophic Ecology of Scleractinian Corals - Michael P. Lesser; Marc Slattery; Keir J. Macartney (Oceans, 2022)
Studies on the trophic ecology of scleractinian corals often include stable isotope analyses of tissue and symbiont carbon and nitrogen. These approaches have provided critical insights into the trophic sources and sinks that are essential to understanding larger-scale carbon and nitrogen budgets on coral reefs. While stable isotopes have identified most shallow water (<30 m) corals as mixotrophic, with variable dependencies on autotrophic versus heterotrophic resources, corals in the mesophotic zone (~30–150 m) transition to heterotrophy with increasing depth because of decreased photosynthetic productivity. Recently, these interpretations of the stable isotope data to distinguish between autotrophy and heterotrophy have been criticized because they are confounded by increased nutrients, reverse translocation of photosynthate, and changes in irradiance that do not influence photosynthate translocation. Here we critically examine the studies that support these criticisms and show that they are contextually not relevant to interpreting the transition to heterotrophy in corals from shallow to mesophotic depths. Additionally, new data and a re-analysis of previously published data show that additional information (e.g., skeletal isotopic analysis) improves the interpretation of bulk stable isotope data in determining when a transition from primary dependence on autotrophy to heterotrophy occurs in scleractinian corals.